Temperature‐Dependent Optical Properties of CsCu2I3 Perovskites - Giovanni Vescio; Joshua Diago Forero; Paolo Pellegrino; Sergio García de Mendoza; Robert Oliva; Jordi Ibáñez; Blas Garrido; Albert Cirera; Sergi Hernández (Advanced Materials Interfaces, 2025)
Abstract This study examines the temperature‐dependent optical properties of CsCu2I3 nanocrystals using photoluminescence (PL) and optical transmittance techniques. The nanocrystals are synthesized by dissolving CsI and CuI in N,N‐dimethylformamide, varying the synthesis temperature and oleic acid volume. X‐ray photoelectron spectroscopy (XPS) and X‐ray diffraction (XRD) confirm the stoichiometry and crystalline structure, with optimal synthesis conditions found at 80 °C and 0.8 mL of oleic acid. Transmittance measurements from 10 K to room temperature shows a redshift in the optical absorption edge with increasing temperature. PL emission, observes in the yellow range, exhibited a blueshift as temperature rose. The emission intensity varied with excitation energy (3.81 eV vs. 4.13 eV): at 4.13 eV, intensity monotonically decreased, whereas at 3.81 eV, it peaked at 190 K, suggesting resonant excitation conditions. By analyzing the temperature‐dependent PL intensity, the exciton binding energy and self‐trap depth energy are estimated. These findings contribute to developing a quantitative model of energy levels in CsCu2I3 perovskites, highlighting their potential applications in optoelectronics. These results provide new insights into the fundamental optical mechanisms in CsCu2I3 perovskites, reinforcing the significance of lead‐free perovskites for sustainable light‐emitting applications and offering valuable knowledge about their optical properties.